Incidence of musculoskeletal injuries in professional soccer players from Aracaju/SE-Brazil. - João Bourbon de Albuquerque II; Walderi Monteiro da Silva Júnior; Matheus Melo Barreto; José Guilherme Vieira Bonfim; Marco Antônio Prado Nunes (Universidade Estadual Paulista (UNESP), 2017)
Abstract AIMS To verify the incidence of injuries in professional soccer athletes in Aracaju-SE and to identify associated factors. METHODS This was an observational, prospective cohort study involving 39 healthy athletes, followed for seven months and evaluated on four occasions (start on preseason and two evaluations with three months of interval between each) through data collection sheet and orthopedic physical examination. RESULTS Participants were 20 athletes from Club Sportivo Sergipe and 19 from Associação Desportiva Confiança, with mean age of 26 years (CI 95%: 25.2-28 years), and mean career time of 9.6 years (CI 95%: 7.9-11.3 years). The 13 (2.4 / 1000 hours) diagnosed injuries occurred almost exclusively in the lower limbs and thigh muscle stretch was the most common injury. Injuries were mostly mild to moderate (69%). There was no significant association with any of the variables analyzed. CONCLUSION Low incidence of injuries was observed in this study. Predominantly, lesions occurred on non-rainy days and were due to trauma. Lower limbs were the most affected location and thigh stretch was the most common injury.